Mechanism of Resveratrol-mediated Suppression of Tissue Factor Gene Expression - Pendurthi, Usha R.; Meng, Feng; Mackman, N.; Rao, L. Vijaya Mohan (Thrombosis and Haemostasis, 2002)
Tissue factor (TF) is a cell surface receptor for factor VII(a), and the binding of factor VII(a) to TF initiates the coagulation cascade. Inappropriate in vivo expression of TF in vascular cells has been shown to be responsible for thrombotic disorders associated with a variety of pathological conditions, including gram-negative sepsis, cancer and atherosclerosis. A number of epidemiological studies suggest that moderate consumption of red wine provides protective effects against coronary heart disease mortality. Recently, we have shown that resveratrol, a polyphenolic compound found in wine, inhibited the induction of TF expression in endothelial cells and mononuclear cells (Pendurthi UR, Williams JT, Rao LVM. Arterioscler Thromb Vasc Biol 1999; 19: 419-426). In the present study, we examined the mechanism by which resveratrol inhibits the expression of TF in monocytes by using a monocytic cell line, THP-1, as a model cell. Northern blot analysis, gel mobility shift assays and transfection studies with various TF promoter constructs, as well as other transcription regulatory constructs, were used to elucidate the inhibitory mechanism of resveratrol. The data show that resveratrol inhibited lipopolysaccharide (LPS)-induced expression of TF in human monocytes and monocytic cell line, THP-1 in a dose dependent manner. Resveratrol did not significantly alter the binding of various transcription factors involved in TF gene expression to DNA. However, resveratrol suppressed the transcription of cloned human TF promoter. Further experiments revealed that resveratrol reduced κB- but not AP-1-driven transcriptional activity. Additional experiments showed that resveratrol suppressed the phosphorylation of p65 and its transactivation. In summary, our results indicate that resveratrol does not inhibit the activation or translocation of NF-κB/Rel proteins but inhibits NF-κB/Rel-dependent transcription by impairing the transactivation potential of p65.
Keywords: Tissue factor; monocytes; gene expression; resveratrol; cardiovascular diseases